2022
DOI: 10.1038/s41531-022-00370-3
|View full text |Cite|
|
Sign up to set email alerts
|

Nitrosative stress in Parkinson’s disease

Abstract: Parkinson’s Disease (PD) is a neurodegenerative disorder characterized, in part, by the loss of dopaminergic neurons within the nigral-striatal pathway. Multiple lines of evidence support a role for reactive nitrogen species (RNS) in degeneration of this pathway, specifically nitric oxide (NO). This review will focus on how RNS leads to loss of dopaminergic neurons in PD and whether RNS accumulation represents a central signal in the degenerative cascade. Herein, we provide an overview of how RNS accumulates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 190 publications
0
15
0
Order By: Relevance
“…However, the relative contribution and differential role of oxidative stress at different stages of the development and progression of NDDs remains poorly understood 55 . One major hallmark of oxidative stress in NDDs is the preferential accumulation of nitrated misfolded proteins in the proteinaceous pathological inclusions found in the brains of affected patients 2, 7, 56 . This has led to the suggestion that oxidative modifications of aggregation-prone proteins may play causative roles in the initiation and/or progression of protein misfolding, aggregation, pathology spreading, or neurodegeneration in NDDs 20, 57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the relative contribution and differential role of oxidative stress at different stages of the development and progression of NDDs remains poorly understood 55 . One major hallmark of oxidative stress in NDDs is the preferential accumulation of nitrated misfolded proteins in the proteinaceous pathological inclusions found in the brains of affected patients 2, 7, 56 . This has led to the suggestion that oxidative modifications of aggregation-prone proteins may play causative roles in the initiation and/or progression of protein misfolding, aggregation, pathology spreading, or neurodegeneration in NDDs 20, 57 .…”
Section: Discussionmentioning
confidence: 99%
“…In these diseases, the production of reactive oxygen (ROS) and nitrogen (RNS) species overwhelms the antioxidant capacity of cells 5 , leading to a redox imbalance and ultimately to increased production of the nitrogen dioxide radical (NO 2 ˙), 3-nitrotyrosine, and dityrosine cross-linking formation 3,6 . Several neuropathological observations and recent rodent studies also suggest this to be the case in Parkinson's disease (PD) [7][8][9] , the second most common age-related NDD.…”
Section: Introductionmentioning
confidence: 96%
“…Oxidative and nitrative stress in the mesencephalon, where dopaminergic neurons are located, is one of the main factors related to PD pathogenesis [ 20 , 21 ]. Dopamine is susceptible to auto-oxidization, producing toxic semiquinone species, H 2 O 2 , and a small amount of the neurotoxin 6-hydroxydopamine [ 22 , 23 ].…”
Section: Metals Parkinson’s Disease and Oxidative Stressmentioning
confidence: 99%
“…The exact mechanism is not clear, but excess calcium produces superoxides, which in the presence of NO produce peroxy nitrates and inactivate MCI. 112,113 3.5. Endoplasmic Reticulum Stress, Calcium Overload, and MCI Dysfunction.…”
Section: Oxidative Stress and MCI Dysfunction Oxidative Stress Arises...mentioning
confidence: 99%
“…In PD, studies have shown increased nitrosative stress. The exact mechanism is not clear, but excess calcium produces superoxides, which in the presence of NO produce peroxy nitrates and inactivate MCI. , …”
Section: Role Of MCI Dysfunction In Pdmentioning
confidence: 99%